2012
DOI: 10.1152/ajpregu.00597.2011
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of vH+-ATPase is part of the functional adaptation of sheep rumen epithelium to high-energy diet

Abstract: Ruminal vacuolar H(+)-ATPase (vH(+)-ATPase) activity is regulated by metabolic signals. Thus, we tested whether its localization, expression, and activity were changed by different feeding. Young male sheep (n = 12) were either fed hay ad libitum (h) or hay ad libitum plus additional concentrate (h/c) for 2 wk. The vH(+)-ATPase B subunit signal was predominantly found in the cell membrane and cytosol of rumen epithelial cells (REC) with basal/parabasal phenotype. The elevated number (threefold) of these cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…Upregulation of ATPB in the epithelium of goats in response to energy supply supports the findings of Bondzio et al [8], who have identified ATP5G (ATP synthase subunit gamma) to be up-regulated in sheep fed a concentrate supplemented diet, and suggests an increased energy requirement during enhanced proliferation of germinative epithelial cell layers of the rumen [47] or an increase of electrochemical gradients in response to energy supply [12]. On the other hand, the study demonstrated downregulation of other two enzymes involved in energy metabolism such as NDKB and TPI in response to high energy supply.…”
Section: Discussionsupporting
confidence: 81%
“…Upregulation of ATPB in the epithelium of goats in response to energy supply supports the findings of Bondzio et al [8], who have identified ATP5G (ATP synthase subunit gamma) to be up-regulated in sheep fed a concentrate supplemented diet, and suggests an increased energy requirement during enhanced proliferation of germinative epithelial cell layers of the rumen [47] or an increase of electrochemical gradients in response to energy supply [12]. On the other hand, the study demonstrated downregulation of other two enzymes involved in energy metabolism such as NDKB and TPI in response to high energy supply.…”
Section: Discussionsupporting
confidence: 81%
“…In other studies, higher inclusion of dietary concentrates increased MCT1 protein abundance, both when compared to an all-forage diet (Kuzinski and Rontgen, 2011) and in unrestricted access as compared to restricted access, despite similar SCFA concentrations (Koho et al, 2011). In our study, the increase in MCT1 and NHE3 on epithelial cells appears to be primarily aimed at maintain-ing intracellular pH.…”
Section: Effect Of Timesupporting
confidence: 53%
“…triphosphatase (vH + -ATPase), a sensor of substrate and energy availability participating in H + translocation across limiting membranes and of the peroxisome proliferatoractivated receptor isoform-α (PPARα) involved in energy homeostasis and in cell cycle, has been estimated in proliferated epithelial cells in rumen with higher butyrate concentrations (Kuzinski et al, 2012;Naeem et al, 2012;Connor et al, 2013). The process of cell division is connected with pHi changes which are induced metabolically (Madshus, 1988).…”
mentioning
confidence: 99%
“…The butyrateinduced acid load in the ruminal epithelial cells stimulates the activities of proteins involved in the pHi recovery to the values of cell homeostasis. These pH-homeostatic mechanisms include membrane-bound transporters belonging to the solute-carrier family, isoforms of (monocarboxylate transporter (MCT)), sodium-proton exchangers (NHEs) and also P-type cation transport adenosine triphosphatases (Graham et al, 2007;Kuzinski et al, 2012). It has been recognized that an increasing ruminal concentration of butyrate stimulates the activities of proton-linked monocarboxylate transporter isoform 1 (MCT1) and/or isoform 4 (MCT4) in transporting carboxylic acids in the ruminal epithelial cells in calves (Laarman et al, 2012), goats (Yan et al, 2014) and lambs (Malhi et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation